Immunization Status of Children Admitted to a Tertiary-care Hospital of North India: Reasons for Partial Immunization or Non-immunization - Kumar, Devendra; Aggarwal, Anju; Gomber, Sunil (Journal of Health, Population and Nutrition, 2010)
Reasons for the low coverage of immunization vary from logistic ones to those dependent on human behaviour. The study was planned to find out: (a) the immunization status of children admitted to a paediatric ward of tertiary-care hospital in Delhi, India and (b) reasons for partial immunization and nonimmunization. Parents of 325 consecutively-admitted children aged 12-60 months were interviewed using a semi-structured questionnaire. A child who had missed any of the vaccines given under the national immunization programme till one year of age was classified as partially-immunized while those who had not received any vaccine up to 12 months of age or received only pulse polio vaccine were classified as non-immunized. Reasons for partial/non-immunization were recorded using open-ended questions. Of the 325 children (148 males, 177 females), 58 (17.84%) were completely immunized, 156 (48%) were partially immunized, and 111 (34.15%) were non-immunized. Mothers were the primary respondents in 84% of the cases. The immunization card was available with 31.3% of the patients. All 214 partially- or completely-immunized children received BCG, 207 received OPV/DPT1, 182 received OPV/DPT2, 180 received OPV/DPT3, and 115 received measles vaccines. Most (96%) received pulse polio immunization, including 98 of the 111 non-immunized children. The immunization status varied significantly (p<0.05) with sex, education of parents, urban/rural background, route and place of delivery. On logistic regression, place of delivery [odds ratio (OR): 2.3, 95% confidence interval (CI) 1.3-4.1], maternal education (OR=6.94, 95% CI 3.1-15.1), and religion (OR=1.75, 95% CI 1.2-3.1) were significant (p<0.05). The most common reasons for partial or non-immunization were: inadequate knowledge about immunization or subsequent dose (n=140, 52.4%); belief that vaccine has side-effects (n=77, 28.8%); lack of faith in immunization (n=58, 21.7%); or oral polio vaccine is the only vaccine required (n=56, 20.9%. Most (82.5%) children admitted to a tertiary-care hospital were partially immunized or non-immunized. The immunization status needs to be improved by education, increasing awareness, and counselling of parents and caregivers regarding immunizations and associated misconceptions as observed in the study. Key words: Child; Immunization; Vaccination; India DOI: 10.3329/jhpn.v28i3.5560 J HEALTH POPUL NUTR 2010 Jun;28(3):300-304